Islamophobia Agenda in Islamist Magazines in Türkiye: A Content Analysis - Mücahit Sami Küçüktığlı (Medya ve Din Araştırmaları Dergisi)
The presence and capabilities of religious groups in Turkey, particularly in terms of their propaganda power, is an undeniable reality. These groups have a well-established institutional infrastructure in magazine publishing, and the magazine industry has successfully transitioned into the digital realm. However, there is a lack of sufficient studies in the literature concerning the role of Islamist magazines in Turkey in addressing Islamophobia on a global scale. Religious groups in Turkey have historically and culturally established strong ties with society, particularly in utilizing magazines as a tool for propaganda. In this context, the study examines the theme of Islamophobia, which has become increasingly widespread globally, especially in Europe and the United States, in the magazines published by religious groups in Turkey. Using a qualitative methodology, the article analyzes the publications of the five major religious groups in Turkey, focusing on the concept of Islamophobia. The data collected has been examined through semiotic analysis and content analysis techniques. The findings of the study reveal that religious groups exhibit shortcomings in publishing articles that generate counterarguments to Islamophobia and in utilizing global language in their magazine publications. It is believed that this study will contribute to future research on the relationship between religious groups, Islamophobia, propaganda, and digital communication.